Studi Eksplorasi Tentang Harapan Masyarakat terhadap Keberadaan Aset Wisata Embung Tambakboyo Kabupaten Sleman Daerah Istimewa Yogyakarta - Agus Wibowo SBS (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2012)
Water Resources must be managed in a comprehensive, integrated and environmentally sound in order to realize the benefit of sustainable water resources for the prosperity of society. For the participation in exploring the public’s expectations of the existence of an asset for tourism Embung Tambakboyo together to built awareness and understanding in the management of water resources in order to have available economic value for sales to tourists. Three things in this effort are I. The changing social function of the water from the objects to objects that have economic value, 2. The changing nature of the waters Public Property inti an economic commodity that can be controlled by private owners, 3. Shifting role of government from provider to facilitator. From the analysis can be concluded that based on the variables of economic, social and community participation of the three community groups (MU, PKL, KET). An increase in the economy is the main hope of street vendors and community groups have the highest expectations compared to the MU and KET. Be comprehensive to date has been the existence of Embung Tambakboyo has many positive benefits for local peoples, social and environmental sector economic and Embung Tambakboyo worthy of man-made attractions.